2023
DOI: 10.53771/ijstra.2023.4.1.0042
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical effects of some preservatives on Glycine max in adult male albino rats

Abstract: The food insecurity problem in Nigeria is largely due to the inability to preserve food surpluses after harvest. Post-harvest loss of grains account for between 5-25% forcing farmers’ use of some pesticides. This study examines the Biochemical effects of some preservatives on Glycine max in adult male albino rats. Glycine max (soya beans) sample was collected from Keffi Area of Nasarawa state, divided into five groups and preserved with Aluminum Phosphide, Dichlorvos (sniper), Wood-ash and Pepper while the fif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…[50][51][52][53][54][55][56] observed significant enhancements in employment, income, and overall livelihood when implementing pig-based IFS and crop-fish-duck systems compared to sole cropping. Likewise, [8,7,10,16,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] demonstrated that adopting IFS offers a promising and financially rewarding alternative to existing cropping systems, delivering higher returns, water productivity, employment opportunities, and energy output.…”
Section: Effect Of Ifs On Employment Generationmentioning
confidence: 99%
“…[50][51][52][53][54][55][56] observed significant enhancements in employment, income, and overall livelihood when implementing pig-based IFS and crop-fish-duck systems compared to sole cropping. Likewise, [8,7,10,16,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] demonstrated that adopting IFS offers a promising and financially rewarding alternative to existing cropping systems, delivering higher returns, water productivity, employment opportunities, and energy output.…”
Section: Effect Of Ifs On Employment Generationmentioning
confidence: 99%
“…Flooded conditions in traditional systems promote reduced iron availability and the transformation of phosphorus into less soluble forms. In DSR, the relatively aerobic conditions can influence nutrient cycling processes, impacting the availability of essential nutrients like nitrogen and phosphorus [8].…”
Section: Nutrient Dynamics In Direct Seeded Rice Systemsmentioning
confidence: 99%
“…From the incorporation of pheromone traps and genetically modified crops to the use of data analytics and precision agriculture, IPM strategies have become increasingly sophisticated. This modern era of IPM not only addresses the immediate need for pest control but also focuses on longterm sustainability, ecological balance, and food safety [20].…”
Section: Initial Adoption Of Ipm Was Driven By Academia and Forwardth...mentioning
confidence: 99%